Revealing the spin–vibronic coupling mechanism of thermally activated delayed fluorescence - Marc K. Etherington (Nature Portfolio, 2016)
Knowing the photophysics of thermally-activated delayed fluorescence (TADF) is crucial when designing organic light emitting diodes. Here the authors show that spin orbit coupling in TADF materials is described by a second order vibronic coupling mechanism, and demonstrate the importance of resonance effects to achieve efficient TADF.